Internal Working Conditions and Well-being of Bank Employees during the Pandemic: A Case Study of Yogyakarta City - Bagoes Setiawan (Journal of Economics Research and Social Sciences, 2022)
Since the pandemic conditions, the well-being of employees in Indonesia has continued to decline. The Work Trend Index survey from Microsoft stated that the level of employee well-being reached 68% in 2019, which then dropped to 61% in 2021. This decline in well-being is inseparable from the relationship between the company and employees, manifested in the internal work situation. This study aims to identify the influence of internal working conditions on the well-being of employees, especially in the banking sector, considering the pressure and work stress are pretty heavy. Banking employees are vulnerable to work stress due to high pressure, competition, and demands to provide the best service. Specifically, This study compares the well-being of employees in conventional and Islamic banks, considering that there are differences in the work system between the two. The city of Yogyakarta was then chosen as the object of this research because of the low City Minimum Wage (UMK) of Yogyakarta compared to the five other provincial capitals on the island of Java. The data obtained through a questionnaire from as many as 107 respondents were then processed using multiple regression analysis. The finding of this study is that the well-being of conventional bank employees is statistically higher than that of Islamic banks. In general, work pressure has a negative and significant effect on well-being. Like income, work motivation also positively and significantly impacts well-being.